2011
DOI: 10.1177/0165551511401658
|View full text |Cite
|
Sign up to set email alerts
|

Are the abstracts of high impact articles more readable? Investigating the evidence from top research institutions in the world

Abstract: This paper examines the abstracts of the articles of the five most cited institutions in the world to determine their text reading level. Around 260,000 articles were analysed during 2000-2009 and the Flesch reading ease (RE) formula was applied to calculate the difficulty level of the abstracts according to the readability scores. The present study tries to: determine the abstracts reading level; discover the difference in the abstracts reading level among various disciplines; check the changes in the reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 25 publications
6
41
0
3
Order By: Relevance
“…However, previous research confirmed a negative correlation between the abstract readability and citation impact of publications in the top institutions of the world (Gazni, 2011). There are numerous readability measures available but each of them has its own limitations (Gazni, 2011). To prevent the limitations of a single measure to negatively affect the results of the current study, a range of readability formulae was chosen to examine their associations with citation counts.…”
Section: Abstract Readabilitymentioning
confidence: 86%
See 4 more Smart Citations
“…However, previous research confirmed a negative correlation between the abstract readability and citation impact of publications in the top institutions of the world (Gazni, 2011). There are numerous readability measures available but each of them has its own limitations (Gazni, 2011). To prevent the limitations of a single measure to negatively affect the results of the current study, a range of readability formulae was chosen to examine their associations with citation counts.…”
Section: Abstract Readabilitymentioning
confidence: 86%
“…The Spearman correlation between this variable and citation counts is close to zero in the three fields, although it is a negative correlation coefficient in Biology & Biochemistry and Chemistry but positive in Social Sciences. However, previous research confirmed a negative correlation between the abstract readability and citation impact of publications in the top institutions of the world (Gazni, 2011). There are numerous readability measures available but each of them has its own limitations (Gazni, 2011).…”
Section: Abstract Readabilitymentioning
confidence: 98%
See 3 more Smart Citations